Online Instructional Personal Environment for Deep Language Learning - Francois Victor Tochon; A. Cendel Karaman; Celile E. Ökten (Informascope, 2014)
This article focuses on the creation of instructional materials that serve as a personal environment for learning a less-commonly-taught language. The study aims to raise awareness of ways in which digital personal learning environments can be used in tandem with more formal learning strategies. The study explores self-regulated language learning within personal environments created for intermediate and advanced Turkish. We reviewed the conceptual background for the approach as well as the project-based learning strategies scaffolded in the online thematic materials. Through a 3-year longitudinal inquiry and semi-structured interviews with eight instructors who implemented the approach in four universities, the authors analyze the impact of personalized learning in developing deeper levels of language apprenticeship. The instructors we interviewed report increased growth in proficiency and accuracy in linguistic and cultural learning, as experienced in their courses through their formative and summative assessments, as well as the realization of most pedagogical goals related to language acquisition in a rich format. In light of the needs for teacher education adapted to new technologies, the paper highlights the difficulties of pedagogy for autonomy.